O abastecimento alimentar em Fortaleza (CE) a partir da dinâmica dos produtos hortifruti e da central de abastecimento do Ceará S/A(Ceasa-Maracanaú) - Macêdo, Rebeka Carvalho (2023)
The Ceará Supply Center (Ceasa-Maracanaú) located in the Metropolitan Region of Fortaleza (RMF), in the municipality of Maracanaú, was founded in 1972, being a mixed economy company, with the objective of centralizing the distribution of the production of the hortifruti segment, as well as other products. It presents itself as one of the main elements for the food supply of cities. This research aims to understand the process of food supply in Fortaleza (CE), through the dynamics of hortifruti products and the Central Supply of Ceará S /A (Ceasa-Maracanaú). The CEASA is the central point of convergence, distribution and marketing for the main equipment for supplying these products. The research methodology is of a qualitative-quantitative nature with emphasis on bibliographic review, documentary analysis, survey of secondary and primary data. The fieldwork was carried out at CEASA (Ceasa-Maracanaú), São Sebastião Market, some supermarket chains and urban gardens of Fortaleza, for the application of interviews. As research criteria were selected the ten main products marketed in terms of volume and value collected in the Central Supply (Ceasa-Maracanaú) that supply the metropolis of Fortaleza of which we investigated the amount in tons, the values in reais and the origin and final destination. Among the main products marketed, considering the period from 2002 to 2022, are: avocado, pineapple, silver banana, English potato, pear onion, carrot, orange, watermelon, cabbage and tomato that represent 70% of the average supply of 397 thousand tons per year. The results of the research indicate that CEASA (Maracanaú - CE) plays a strong role in the supply of in natura products of Fortaleza, supplying both the upper and lower circuits of the Urban Economy. This structure has benefited family farmers, marketers and small grocery stores and local supermarket chains, despite the growing and strong monopoly of supermarket chains that compete nationally and internationally in the marketing of these foods. The CEASA (Maracanaú - CE) presents numerous structural, logistical and technological challenges that need to be remedied, however, we observe its importance as a centralizing structure of productions in the different geographical scales, from global to local, and that contribute to the flow of the productions of family agriculture and the guarantee of food and nutritional security of the population of Fortaleza.